Brazilian coal tailings projects: advanced study of sustainable using FIB-SEM and HR-TEM (2022)
The objective of this study is to obtain a more detailed assessment of particles that contain rare-earth elements (REEs) in abandoned deposits of Brazilian fine coal tailings (BFCTs), so as to aid current coal mining industries in the identification of methodologies for extracting such elements (Santa Catarina State, Brazil). The BFCT areas were sampled for traditional mineralogical analysis by X-ray Diffraction, Raman Spectroscopy and nanomineralogy by a dual beam focused ion beam (FIB) coupled with field emission scanning electron microscopy (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM) coupled with an energy dispersive X-ray microanalysis system (EDS). The results show that the smaller the sampled coal fines were, the higher the proportion of rare-earth elements they contained. Although the concentration of REEs is below what would normally be considered an economic grade, the fact that these deposits are already ground and close to the surface negate the need for mining (only uncovering). This makes it significantly easier for REEs to be extracted. In addition, owing to their proximity to road and rail transport in the regions under study, the opportunity exists for such resources (BFCTs) to be utilized as a secondary market as opposed to simply being discarded as has been done in the past.